Foresight, Competitive Intelligence and Business Analytics — Tools for Making Industrial Programmes More Efficient - Jonathan Calof; Gregory Richards; Jack Smith (Foresight and STI Governance)
Creating industrial programmes, especially in technology, is fraught with high levels of uncertainty. These programmes target the development of products that will not be sold for several years; therefore, one of the risks is that the products will no longer be in demand due to the emergence of more advanced technologies. The paper proposes an integrated approach involving the complementary functions of foresight, intelligence and business analytics. The tools of foresight and intelligence are focused on the external environment and enable industry and researchers to, among other things, understand the direction in which markets and technologies are evolving, and profile local industries to determine which policy instruments may be effective in these industries. Signals picked up today through externally focused intelligence studies can be used to confirm conclusions from longer term foresight initiatives such as scenarios, roadmaps and scans, thereby providing the information needed to establish the long-term industrial policy that science and technology related industries require.